Performance Evaluation of Android Applications: A Case Study - Fernandes, Thiago Soares; Cota, Érika; Moreira, Álvaro Freitas (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2014)
Mobile applications development is guided by the careful attention to a number of non-functional requirements, where a good user experience is the ultimate goal. As part of this effort, the developer needs to efficiently use the physical resources of the mobile device, such as CPU time and battery. However, up until now, there is no structured method for performance evaluation in this domain that provides actionable information to the software developer. We present two case studies regarding the performance evaluation process for mobile applications and its impact on development.